Edukasi Peralatan Pengukuran dengan Metode Praktikum di Sma Negeri 27 Maluku Tengah - Delpina Nggolaon; Silahooy, Stevi; Jaya, Gede Wiratma (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Physics is one of the subjects that is the basic foundation for the development of science and technological progress. In physics learning, emphasis is placed on the process of forming knowledge through discovery and the presentation of regular data supported by practical activities. However, in reality there are still many schools that do not carry practical physics activities. Therefore, this dedication regarding measuring equipment education using practical methods for students at SMA Negeri 27 Central Maluku aims to help students in learning so they can improve learning outcomes and provide information about appropriate learning methods. This service activity was carried out on 21 class X students who had previously studied the same material conventionally from their teachers. The Community Service (PKM) activities employ the service-learning method, which consists of four stages: investigation, preparation, action, and reflection. The results of educational service activities can be shown by data on initial scores (pre-test) and final scores (post-test) obtained by students, namely an average initial score of 20.48 and an average final score of 65.24. These results show a significant increase in learning outcomes. In this way, educational service activities for measuring equipment using the practicum method have been carried out well. This is also demonstrated by the students' enthusiasm in participating in practicum activities.